ACE inhibitory casein peptide lowers blood pressure and reshapes gut microbiota in a randomized double blind placebo controlled trial - Li, Kexin; Jiang, Peng; Li, Shuangqi; Sun, Jin; Qi, Ce (Scientific reports, 2025)
Casein-derived peptides have been shown to reduce blood pressure in animal studies, but evidence from human trials remains limited. This study aimed to investigate the antihypertensive effect and possible mechanisms of a hydrolyzed casein peptide tablet containing GPFPIIV and FFVAPFPEVFGK (HCP-C7C12) in prehypertensive/hypertensive patients. In this double-blind, randomized, placebo-controlled clinical trial, 131 participants were recruited and randomly allocated to either the test product group (HCP) taking tablets containing HCP-C7C12 or the placebo group for an eight-week intervention. 114 participants finally completed the study. After the intervention, both the systolic blood pressure and diastolic blood pressure in the HCP group were significantly reduced ( P < 0.01) by 9.41% and 9.53%, respectively. The antihypertensive mechanisms may involve (1) HCP-C7C12 acting as an angiotensin-converting enzyme inhibitor, reducing angiotensin II production, and (2) modulating amino acid abundance such as L-Arginine, L-valine, leucine, and phenylalanine, resulting in anti-inflammatory and antioxidant effects that improve endothelial function. Additionally, HCP-C7C12 exhibited prebiotic-like effects, activating the butyrate and propionate production pathway and increasing the abundance of gut microbes with anti-inflammatory potentials. Overall, long-term consumption of the HCP-C7C12 tablet could be advantageous for blood pressure control in prehypertensive or hypertensive individuals.